Autotrophic and heterotrophic indicators of ecological impairment in Toronto Harbour and coastal Lake Ontario. Issue 3 (3rd July 2018) - Munawar, M.; Fitzpatrick, M.; Niblock, H.; Lorimer, J.
Abstract : The Toronto and Region Area of Concern (also known as Toronto Harbour) includes 42 km of Lake Ontario coastline and 6 watersheds. Over 4 million people reside within its boundaries which includes the City of Toronto (Ontario, Canada). We sampled eleven sites along the Lake Ontario coastline approximately monthly with 6 cruises from May to early November. Our analyses included standard water quality indicators (total phosphorus, nitrate + nitrite, chlorophyll a ) in addition to a robust suite of autotrophic and heterotrophic indicators of ecosystem health, specifically: primary productivity and bacterial growth assays, phytoplankton biomass assessments, and microbial loop assessments. The sites were compared using mean values from May – November. Results from the offshore waters of Lake Ontario, the Bay of Quinte and Hamilton Harbour have also been presented for comparative purposes. The highest mean values observed in Toronto Harbour for total phosphorus (26.5 µg l −1 ) and chlorophyll a (6.2 µg l −1 ) which were both in the inner harbour suggested mesotrophic conditions, although the majority of observations suggested oligotrophy. With respect to autotrophic indicators, primary productivity at the mouth of the Humber River as well as the inner harbour (averaging 15 – 20 mg C m −3 h −1 ) suggested mesotrophy whereas the remaining sites were more oligotrophic. Phytoplankton biomass (≈400 – 1000 mg m −3 ) suggested oligotrophy. There was a surprising amount of heterotrophic microbial activity at the Humber Bay and inner harbour sites which were influenced by the Humber and Don Rivers. This included elevated rates of bacterial production (≈2 – 3 mg C m −3 h −1 ) and a high biomass of heterotrophic nanoflagellates (≈1300 – 2600 mg m −3 ) which was not likely sustained by the autotrophic production. Our findings suggest that a significant amount of organic matter is being deposited by these two rivers and shunted to the microbial food web. Such findings are not obvious from standard indicators (e.g. total phosphorus, chlorophyll a ). More work is needed to quantify the sources of organic carbon and assess its utility as ecological indicators.